Analisis Dinamika Keterampilan Kognitif dan Non-kognitif terhadap Pilihan Karier pada Sektor Formal di Indonesia - Saskia Nurul Aida Pursari; Muhamad Fajar Asidiq Ramdan; Adinda Chika Tris Winanti; Eva Ervani (Jurnal Pemimpin Bisnis Inovatif, 2025)
Cognitive and non-cognitive abilities are essential indicators in assessing an individual's human resource (HR) capacity. Cognitive abilities refer to intellectual potential, while non-cognitive abilities encompass social and emotional aspects. This study aims to analyze the relationship between cognitive and non-cognitive skills and preferences for formal or informal employment sectors. The research utilizes secondary data from the Indonesian Family Life Survey (IFLS) conducted in 2014 and employs a probit regression method with several control variables. The analysis reveals that cognitive skills have a significantly positive association with the likelihood of working in the formal sector. These findings provide valuable insights into the role of individual skills in determining employment sector choices.